Myanmar Monthly Food Price Report – September 2025 - Htar, May Thet; Minten, Bart; Masias, Ian (International Food Policy Research Institute, 2025)
Rice prices in September 2025 declined nationally, falling by 8 percent year-on-year and 5 percent compared to the previous month. The decrease was driven by international market trends and downward pressure from the incoming monsoon harvest. Prices either stabilized or declined across most states and regions in the country. Export crop prices diverged, with green gram rising this year due to strong international demand, while black gram and pigeon pea declined year-on-year due to reduced demand in India. Animal-sourced food prices surged over the last year – e.g. pork rose by 55 percent – due to rising production costs, while fish prices rose amid strong export demand. Multiple risks lie ahead, including falling international rice prices, ongoing conflict, quality concerns, import restrictions, and disruptions in border trade, all of which may undermine agricultural production, farm income, and food security.